Students and lecturers perception of equity, access and democratization in higher education in Georgia - Khositashvili, Giga; Nana Makaradze; Tamar Aslanishvili (PRATICA - Revista Multimédia de Investigação em Inovação Pedagógica e Práticas de e-Learning, 2022)
As a developing country, there are some challenges in Georgian Higher educational system that are related to equity, access and democratization. In addition to the students coming from ethnic minority groups (with no competences in Georgian language), the majority of the students comes from the peripheral areas and after moving to the big cities they need to work for paying their studies. Distance Education can be seen as a solution of the problems related to access on Higher education, for this reason this study aimed to find out what were the perceptions of the students and faculty members from the three universities (one from capital and two regional state HEIs). After collecting the data with using online surveys some focus groups and in-depth interviews were conducted with staff member, in order to discuss the students survey findings and hear more about teachers’ perceptions regarding the equity/access in Higher Education. The data collection was conducted fully online due to the pandemic (in April-June 2020). The results of the survey, together with the discussion and main findings are given in the following report